Relational Typologies, Assemblage Theory and Early Bronze Age Burials. Issue 1 (11th January 2017) - Fowler, Chris
Abstract : This article argues that artefact types and typologies are kinds of assemblages, presenting an explicitly relational interpretation of typology grounded in a more-than-representational assemblage theory. In the process it evaluates recent approaches to typology, and the interpretations these typologies have supported, and compares these with approaches which emphasize materiality and experience. It then illustrates the benefit of drawing these two angles of analysis closer together within an approach grounded in a more-than-representational assemblage theory. Throughout, the discussion revolves around British Chalcolithic and Early Bronze Age burials and types of artefacts commonly found within them. The core argument is that, if used appropriately, typologies are not constraints to the appreciation of distinctiveness, difference and relationality in the past, but can rather form an important tool in detecting those relations and making sense of different past ways of becoming.